Conservation of plasticized PVC artifacts in museums: Influence of wrapping materials. - Royaux, Adeline; Apchain, Emilande; Fabre-Francke, Isabelle; Balcar, Nathalie; Barabant, Gilles; Bollard, Clémentine; Lavédrine, Bertrand; Fichet, Odile; Cantin, Sophie (Journal of Cultural Heritage, 2020)
The effects of LDPE and PET in contact with heritage object made in PVC were studied and compared with silk paper during an artificial aging consisting in a temperature cycle and under controlled relative humidity. Color changes, morphological changes of the surface, plasticizers loss and surfaces properties were assessed over aging time. More pronounced color changes than for the references (without contact material and with silk paper) are observed for both contact materials but are more significant for PET whose surface has brown spots from three months of aging. The plasticizers cross LDPE from the outset of the aging but zein (protein additive) is evidenced only on the side in contact with the PVC. The PVC sample in contact with PET shows phtalic acid from DOP degradation but it remains on the PVC surface.